Board Game Prototype About the Historical Period of Japanese Colonialism in Indonesia for Middle School Students - Jonathan Winfredo Wongso Soebakti; Bing Bedjo Tanudjaja; Daniel Kurniawan Salamoon (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
The teaching method used in history subjects usually needs a lot of memorizations, considered less interesting and less important compared to other subjects leading to difficulties to memorize the topic. The other reason the students think that history is not too important is because they are more interested in other countries' cultures. This prototype is made mainly for middle school students so that they are motivated and more interested to learn Indonesian history. This prototype uses qualitative research and uses 5W+1H data analysis. With the creation of the Koloni board game, we hope that the students can be more interested in learning and understanding Indonesian history.